Sensory integration difficulties and dysfunctions in children with fetal alcohol spectrum disorders - Du Plooy, Maritha (University of the Free State, 2017)
Introduction: The effects of Fetal Alcohol Spectrum Disorders (FASD) are devastating and enduring, impacting on performance skills and limiting successful participation in activities of daily life. The high prevalence of FASD in the Western Cape, together with poor results in school performance, are reasons for concern. Symptoms of sensory integration dysfunctions are reported as challenges faced by children with FASD. The aim of this study was to describe sensory integration difficulties and dysfunctions experienced in a group of children aged five to eight years old from the Cape Winelands Education District (CWED), both with and without a diagnosis of FASD. Objectives: The main objectives were to investigate sensory modulation, as measured by the Sensory Profiles, and sensory processing and practic abilities, as measured by the SIPT, of an identified group of children with FASD and a matched controlled group without a diagnosis of FASD. A final objective was to identify patterns of sensory integration difficulties and dysfunctions, to describe these findings, and to draw conclusions about the distinctive patterns of sensory integration difficulties and dysfunctions among children with FASD. Methodology: Thirty children with FASD (cases) were compared with a matched sample (controls) without FASD. Standardized measuring instruments, the Sensory Profile (SP), Sensory Profile School Companion (SPSC) as well as the Sensory Integration and Praxis Tests (SIPT), were used in this quantitative, observational, analytical study. Results: Higher percentages of cases than controls experienced challenges in 22 of the 23 categories of the Sensory Profile, with significant differences in nine of the categories. According to the results of the Sensory Profile School Companion, cases experienced more challenges in all 13 of the categories, with significant differences in three. Comparison of the mean scores of the matched sample showed significant differences in eight categories of the SP and three of the SPSC, with the cases performing poorer. The highest percentages of cases in the Definite Difference and Probable Difference ranges were recorded for Sensory Seeking (90% (n=18)), Inattention/Distractibility (85% (n=17)), Auditory Processing (70% (n=14)), Multisensory Processing (85% (n=17)), Registration (62% (n=19)) and Avoiding (62% (n=19)). The identified sensory processing difficulties seemed to occur in multiple sensory systems, ranging from under- to over-responsiveness. It is important to note that sensory processing difficulties were also reported for the controls, although at lower percentage levels. The paired t-test results indicated significant differences between the paired cases and controls in eleven of the seventeen test items of the SIPT, with the cases performing poorer. According to the results, 14 (46.7%) of the cases adhere to the criteria recognised as a Visuo- and Somatodyspraxia pattern of dysfunction. The difficulties and dysfunctions identified by the Sensory Profiles and SIPT could contribute to the challenges experienced in occupations of the children with FASD. Conclusion: Although further research is needed, the results from this study confirm sensory integration difficulties and dysfunctions of the FASD population impacting on their daily functioning and performance. Consistencies with previous research results were found. The outcome of this study has clinical importance for occupational therapists working with children with FASD, and for educators and caregivers in terms of intervention, education and caring.
Dissertation (M.Occupational Therapy (Occupational Therapy))--University of the Free State, 2017
Keywords: Fetal alcohol spectrum disorders; Occupational therapy; Sensory integration; Occupations; Fetal alcohol syndrome; Alcohol -- Physiological effect